A theoretical study of charge confinement in quantum dots: Modelling the SnO2 charge writing process. - Owen Leyton Williams (2007)
A suite of models is constructed to facilitate the simulation of the SnO[2] charge writing process. In particular, at dimensions where the semiconductor band bending does not fully evolve, this entails the self-consistent solution of the non-linear Poisson equation and the Kohn-Sham equations at non-zero temperature, with the charge in the occupied surface states also self-consistently reconciled with the fundamental electron density generating the confining potential. In this way, a full quantum mechanical treatment of the discrete eigenstates of the quantum dot, inclusive of electron-electron effects, is made, and a Tip-QD-Substrate tunnelling model developed. This work favourably conforms with observed experimental measurements, not only satisfying the recorded data on the ratios of surface state densities far better than existing models, but also offers a tentative explanation for some of the hitherto unsatisfactorily explained sensitivity behaviour of poly crystal line gas sensors on the decrease of the grain radii. It models the charging of a spherical 4nm radius nanocrystal well, with the calculated I-V characteristic clearly exhibiting indications of the Coulomb blockade effect in good agreement with experiment. The calculated maximum electron complement of one nanocrystal of between 81 and 87 injected electrons with a modal potential difference interval between charge transfer events of 0.065V, is in excellent concordance with the experimentally inferred population of 86 elections, charge storage events occurring at intervals of 0.07V.